Plasma Nitriding of Steels - Aghajani, Hossein; Behrangi, Sahand; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on the effect of plasma nitriding on the properties of steels. Parameters of different grades of steels are considered, such as structural and constructional steels, stainless steels and tools steels. The reader will find within the text an introduction to nitriding treatment, the basis of plasma and its roll in nitriding. The authors also address the advantages and disadvantages of plasma nitriding in comparison with other nitriding methods. .
Introduction -- Conventional DC -- Pulsed DC -- RF -- Active screen -- Plasma nitriding methods -- Microstructure -- Mechanical properties -- Corrosion behavior -- Stainless steels (austenitic, martensitic and precipitation hardening stainless steels) -- Tool steels -- Constructional and structural steels -- Microwave plasma nitriding -- Outlook.
Keywords: Metals; Surfaces (Technology).; Thin films; Coatings; Tribology; Corrosion and anti-corrosives.; Plasma (Ionized gases).; Metals and Alloys; Surfaces, Interfaces and Thin Film; Coatings; Tribology; Corrosion; Plasma Physics